2014
DOI: 10.1590/s1519-38292014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura do Sistema de Vigilância Alimentar e Nutricional Indígena (SISVAN-I) e prevalência de desvios nutricionais em crianças Yanomami menores de 60 meses, Amazônia, Brasil

Abstract: Objetivos: analisar a cobertura do Sistema de Vigilância Alimentar e Nutricional Indígena (SISVANI) e estimar a prevalência de desvios nutricionais em crianças menores 60 meses, no Distrito Sanitário Especial Indígena Yanomami (DSEI-Yanomami). Métodos: estudo transversal descritivo, efetuado entre maio/2008 e abril/2009. Para o cálculo da cobertura considerou-se a divisão das crianças avaliadas pelo total de crianças cadastradas e incluíram-se os Pólos-Base com pelo menos um registro de peso e estatura em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
2
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 13 publications
(13 reference statements)
3
12
2
16
Order By: Relevance
“…The high proportion of mothers with short height (< 145cm), approximately 2/3 of the sample studied in this investigation, is compatible with the historic precariousness of the Yanomamis' nutritional situation, which has already been pointed out by other authors at different times and in different scenarios 16,27 , indicating that these adverse processes take place continuously and over a long period. The association between severe stunting in infancy and low height in Yanomami mothers suggests that these height deficits have been repeated for several genera-tions, possibly resulting in premature births and in newborns being less than the expected weight, and small for their gestational age 28 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The high proportion of mothers with short height (< 145cm), approximately 2/3 of the sample studied in this investigation, is compatible with the historic precariousness of the Yanomamis' nutritional situation, which has already been pointed out by other authors at different times and in different scenarios 16,27 , indicating that these adverse processes take place continuously and over a long period. The association between severe stunting in infancy and low height in Yanomami mothers suggests that these height deficits have been repeated for several genera-tions, possibly resulting in premature births and in newborns being less than the expected weight, and small for their gestational age 28 .…”
Section: Discussionsupporting
confidence: 89%
“…Although some authors have reported high prevalences of stunting in indigenous children in South America 10,14 and in Guatemala 15 , prevalences above 80% have only been recorded among the Yanomami. Pantoja et al 16 , in a study that evaluated the coverage of the Indigenous Yanomami Territory Food and Nutrition Vigilance System, including the Base Stations of Paapiu and Waikás, reported a prevalence close to 80%, of stunting in children below the age of five, similar to those revealed in this study. Hidalgo et al 17 also reported 72.3% prevalence of stunting in children of this age group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…No presente estudo, a mediana de cobertura do Sisvan Web para crianças menores de 5 anos nos 37 municípios avaliados, no período de setembro a outubro de 2012, foi 5,59%, sendo que os valores de cobertura variaram entre 0,55% e 35,8%. Outros estudos também verificaram baixas coberturas para o Sisvan 13,19,20 . Estudo em que se avaliou a cobertura do Sisvan para crianças menores de dois anos também na SRS-BH, nos anos de 2008 a 2011, verificou baixas coberturas e pouca utilização dos dados do Sisvan.…”
Section: Discussionunclassified